The Impact of Out of classroom education and distance learning on the organisation of dormitory activities - Barna, Viktor (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The study analyzes the experience gained during the distance learning introduced in the spring of 2020 (and partly in the 2020-2021 school year) due to the COVID virus situation. The specific situation has further highlighted that the efficiency of traditional forms of organization and work in dormitories may also decrease, and their application may be optional. Students who are (temporarly) at home are being helped with their school studies and can be addressed mainly with topics that currently or potentially concern them. This paper especially focuses on the aspects of the topic that have arisen in connection with the organization of the topic/phenomenon based activities. Certain parts of this study focus on the fact if the previously organized sessions with personal presence could also take place online. The other parts of the study try to explore if the professional cooperation of dormitory teachers and teacher-student and student-student collaborations could also be maintained online.